At the foot of the Sultan: The dynamic application of shariah in Malaysia - Ismail, S.Z. (Center for Islamic and Middle Eastern Legal Studies (CIMELS), University of Zurich, 2015)
Malaysia is known as one of the 'moderate' Muslim countries in the world. Though Islam is enshrined in the Federal Constitution as the religion of the country, Islamic law does not fully govern the country. In fact, Islamic law is part of the national law, which accommodates civil, Islamic and indigenous laws. Civil laws are statutes of general application and civil courts are for all citizens. However, Muslims are also subjected to Islamic family law which governs all matters related to marriage and divorce and also the Shariah criminal offences law, below which, if violated, the offender can be tried in the state’s Shariah courts. This article seeks to examine the historical background and the development of Islamic law administration in Malaysia. It focuses on the position of Islamic law within the constitutional framework which sets the separation of power between the state and federal governments. It then examines the institutional power, religious bodies, religious authority and the Shariah courts. Lastly, the paper will reflect on the success, challenges and issues of developing Islamic law after more than fifty years since the nation’s independence.